ATH-07 Pre-morbid depression amongst individuals subsequently developing Inflammatory Bowel Disease: a potential co-factor mediating disease onset?. Issue 2 (June 2019) - Blackwell, Jonathan; Saxena, Sonia; Alexakis, Christopher; Cecil, Elizabeth; Bottle, Alex; Petersen, Irene; Hotopf, Matthew; Pollok, Richard
Abstract : Introduction: Patients with depression are at higher risk of later being diagnosed with Inflammatory Bowel Disease (IBD). Some speculate depression results in a pro-inflammatory state, predisposing to the development of IBD. An alternative explanation may be that patients experience undiagnosed gastrointestinal (GI) symptoms for long periods of time, during which they become depressed before receiving a delayed diagnosis of IBD. We aimed to determine if rates of depression are higher in individuals who subsequently develop IBD compared to the background population after adjustment for GI symptoms. Methods: Using a nationally representative research database, we identified incident cases of IBD diagnosed from 1998–2016. A non-IBD control group was matched 4:1 for age and sex. Our primary outcome measures were the prevalence of depression, antidepressant medication (ADM) use and GI symptoms in the year of IBD diagnosis and each of the ten years before. Controls were assigned the IBD diagnosis date of their matched IBD patient as a pseudo-diagnosis date. We used multivariable logistic regression to determine the risk of having depression and/or using an ADM in each of the ten years before IBD diagnosis/pseudo-diagnosis among IBD patients compared with controls. To prevent confounding by delayed of IBD we adjusted for the presence of GI symptoms in that year. Other covariates included age, sex, socioeconomic status and smoking status. Results: We identified 19555 cases of IBD and 78114 non-IBD controls. Depression was more prevalent among IBD patients compared with controls even 9 years prior to diagnosis (2.1% vs 1.8%, p=0.03). There was an excess of ADM use among IBD patients compared with controls as long as 9 years before diagnosis (4.9% vs 4.4%, p=0.03). GI symptoms were more common among IBD patients even 10 years before diagnosis (6.3% vs 4.4%, p<0.01). Multivariable regression demonstrated patients who went on to be diagnosed with IBD were more likely to use ADMs as far as 7 years before diagnosis (OR 1.12, 95%CI 1.02–1.22, p=0.01). Conclusions: This is the first study to demonstrate the higher prevalence of depression and ADM use in IBD patients as long as 9 years before diagnosis. Some patients have GI symptoms up to a decade before receiving a diagnosis of IBD, suggesting delayed diagnosis is longer and more common than previously believed. Even after adjusting for the presence of GI symptoms, the higher risk of ADM use significantly predates IBD diagnosis, suggesting depression may play a part in mediating the onset of IBD.